HARMONY OF FOLKLORE AND WRITTEN LITERATURE (TAMADDUN NURI JURNALI, 2025)
This article discusses the harmony of folklore and written literature, the expression of Western and Eastern traditions in written literature, the essence of the new concept of man, images and motifs in folklore. Primitive views and mythological worldviews in folklore are analyzed. Also, the use of folklore in the work of Togay Murad and the writer's artistic skill in the synthesis of innovations are recognized.